Efektivitas Kompetensi Digital, Pelatihan Berbasis Teknologi dan Inovasi Pembelajaran terhadap Kinerja Mengajar Dosen ITB Nobel pada Era Hybrid Work - HS, Nurul Fuada Fatima; Firman, Ahmad; Asri, Asri (Al-Buhuts, 2025)
This research aims to analyze the influence of Digital Competence, Technology-Based Training, and Learning Innovation on the Teaching Performance of ITB Nobel lecturers in the hybrid work era. The population in this study were all permanent lecturers at ITB Nobel Makassar who were actively teaching in the current semester, totaling 126 people. In determining the number of samples for this study, the researcher used the Slovin formula, which aims to obtain a proportional and representative sample size for the population. Based on the calculation results, a sample of 96 respondents was obtained, which was considered to have been able to accurately describe the characteristics of the population. This study used multiple linear regression analysis techniques or models with the help of SPSS 25 software. The results showed that the third variable, both partially and simultaneously, had a positive and significant effect on the teaching performance of lecturers, with a contribution of 75.4%. The Learning Innovation variable is the most dominant factor in improving lecturer performance in the digital era. This study provides an empirical contribution to the development of a lecturer performance improvement model based on digital competency and pedagogical innovation, as well as providing practical effectiveness for strengthening human resource capacity in higher education.